1984
DOI: 10.1007/bf02537404
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon transport in chylomicrons and high‐density lipoproteins in rat

Abstract: A lipoprotein system is described that transports gut hydrocarbons of low polarity in chylomicrons of intestinal lymph and plasma to plasma high density lipoproteins (HDL) in rat. Four highly lipophilic aryl and alkyl hydrocarbons [benzo(alpha)pyrene; 1,1,1-trichloro-2,2-bis(p-chlorophenol)ethane (DDT), hexadecane and octadecane] were selected to give a graded range of polarity. Chylomicrons were labeled doubly with radioisotopes in triacylglycerol and a single hydrocarbon by feeding [3H]-glycerol and [14C]hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…A similar overall distribution pattern was seen with 14C-PCB and 14C-DDT. The values obtained for the distribution of DDT in the fractions of rat plasma in vitro correspond to those found in earlier studies (Pocock and Vost 1974;Skalsky and Guthire 1975;Vost and Maclean 1984). On the other hand, 2,2', 4,4', 5,5'-hexachlorobiphenyl (6-[14C]CB), one of the PCB isomers, showed a relatively homogenous distribution among the various lipoprotein fractions in the plasma of rat (Vomachka et al 1983).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A similar overall distribution pattern was seen with 14C-PCB and 14C-DDT. The values obtained for the distribution of DDT in the fractions of rat plasma in vitro correspond to those found in earlier studies (Pocock and Vost 1974;Skalsky and Guthire 1975;Vost and Maclean 1984). On the other hand, 2,2', 4,4', 5,5'-hexachlorobiphenyl (6-[14C]CB), one of the PCB isomers, showed a relatively homogenous distribution among the various lipoprotein fractions in the plasma of rat (Vomachka et al 1983).…”
Section: Discussionsupporting
confidence: 78%
“…This is in contrast to the results of Vomachka et al (1984), who observed a major part of the intravenously injected 6-[ 14C]CB in association with the LDL fraction in rats in vivo. On the other hand, Pocock and Vost (1974) and Vost and Maclean (1984) reported that after peroral application of 14C-DDT to rats, the substance was transported via lymphatic chylomicrons to the plasma, and then transferred selectively from chylomicrons to HDL as well as to protein fractions in plasma. This indicates that the binding of persistent environmental pollutants to plasma fractions may differ significantly depending on the type of substance, dose, way of administration and the animal species used (see e.g.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Massive cytokine production induced by vaccination can also damage endothelial cells. Because adjuvant hydrocarbon oils are known to be incorporated into lipoproteins (40), these abnormal lipoproteins may play a direct or indirect role in endothelial cell damage, leading to thrombosis. The mechanism of autoimmunity in salmon may be consistent with the concept of innate autoimmunity (41).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, PCB and organochlorine pesticides in blood are associated with the protein fraction, but also with lipoproteins (20). Although their binding with lipoproteins is considered as the major mechanism responsible for their accumulation, it may also be partially responsible for their lipotoxicity (21).…”
Section: Introductionmentioning
confidence: 99%